Constants in IFD equation for Pandharpur in Scarcity Zone of Western Maharashtra - Sanglikar, R. V.; Upadhye, S. K.; Pardhe, D. D.; Jadhav, J. D.; Amrutsagar, V. M.; Chary, G. Ravindra (International Journal of Bio-resource and Stress Management, 2018)
The hydrologic phenomena which directly influence the interest of an engineer are rainfall, runoff, flood and drought. The characteristics of rainfall which are of importance for a design engineer are those which are responsible for producing runoff. These characteristics are intensity, duration, frequency of rainfall, time distribution and geographical distribution. Rainfall intensity-frequency-duration equations are required for design of soil and water conservation and runoff disposal structures and for planning flood control projects. The rainfall intensity-duration-return period relationship as I=(KTa) / (t+b)d has been developed for Pandharpur in Solapur district under scarcity zone of Maharashtra. The constants K, a, b and d in this equation are location specific. The values of parameters a and b were determined by using graphical method and the values of K and d by least square method. The daily automatic rain gauge charts of Pandharpur for 27 years were analyzed in the form of annual maximum series of various durations viz. 5, 10, 15, 30 minutes, 1, 3, 6, 12 and 24 hours. The constants K, a, b and d for Pandharpur were found as 3.08, 0.2295, 0.8 and 0.9573 respectively by analyzing daily automatic rain gauge charts of Pandharpur. These constants K, a, b and d are useful in determining the maximum intensity of rainfall which is used in calculation of runoff.